A Decade of Rural Transformation : Lessons Learnt from the Bihar Rural Livelihoods Project—JEEViKA - World Bank Group (World Bank, Washington, DC, 2018)
The objective of this booklet is to document a decade of journey of the Bihar Rural Livelihoods Project (BRLP) from 2006 to 2016 in the one of the poorest states in India. The project was successfully completed and a follow-on project, Bihar Transformative Development Project (BTDP) commenced in 2016 to expand the BRLP model. This booklet is a joint effort of the Bihar Rural Livelihood Promotion Society (BRLPS) (locally known as JEEViKA) and the World Bank and aims to share the lessons learnt with the development practitioners and colleagues around the world who have the same motivation and goals for rural poverty alleviation and transformation for shared prosperity.